2017
DOI: 10.1108/f-04-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Measuring perception about sustainability of building materials in Kosovo

Abstract: Structured AbstractPurpose: The purpose of this article is to explore the development of knowledge about facilities management (FM), in particular, the management of FM services in practice, education and research. The article questions whether we know more about optimal models for in-house or outsourcing FM after 25 years of applied research and development of best practices.Design/methodology/approach: The article is based on literature reviews, case studies and personal experiences from practice for over 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(105 reference statements)
2
8
0
Order By: Relevance
“…RRMU, calculated using the methodologies described in ISO 14040 [86], ISO 14041 [87], ISO 14042 [88], and ISO 14043 [89], denominated life cycle assessment [61], showed that paving had the greatest impact due to the amount of material used. This finding is in line with Giama and Papadopoulos [90] and Hoxha et al [91], who observed the relation between the environmental impact of construction material and the use of resources. The construction industry should opt for the rationalization, durability, and choice of materials with lower environmental impact coefficients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…RRMU, calculated using the methodologies described in ISO 14040 [86], ISO 14041 [87], ISO 14042 [88], and ISO 14043 [89], denominated life cycle assessment [61], showed that paving had the greatest impact due to the amount of material used. This finding is in line with Giama and Papadopoulos [90] and Hoxha et al [91], who observed the relation between the environmental impact of construction material and the use of resources. The construction industry should opt for the rationalization, durability, and choice of materials with lower environmental impact coefficients.…”
Section: Discussionsupporting
confidence: 90%
“…The construction industry should opt for the rationalization, durability, and choice of materials with lower environmental impact coefficients. To that end, the choice of materials in the pre-construction phase, using pollution prevention criteria, waste reduction, and incorporated energy were essential for sustainability [91].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2 The similarities of findings from previous studies (Sources: 1 = Abdel-malak, et al [22]; 2 = Ajayi, et al [3]; 3 = Hoxha, et al [8]; 4 = Akadiri and Olomolaiye [23]; 5 = Krueger, et al [24]; 6 = Hoxha and Shala [25]; 7 = Jailani, et al [26]; 8 = Oduyemi and Okoroh [27]; 9 = Mahmoudkelaye, et al [28]; 10 = Danso [29].…”
Section: A Sustainable Criteria For Decision Making (Grounded Theory)supporting
confidence: 66%
“…Because it caused difficulties for project stakeholders in selecting the best material. Based on Hoxha et al [8], it is argued that different stakeholders have different backgrounds in their activities about the criteria for sustainable building materials. Hence, there are no right or wrong criteria to be selected for sustainable building materials.…”
Section: Introductionmentioning
confidence: 99%
“…(Herda et al, 2017), considering the problem of comparing construction products and switching to sustainable construction in Kenya, pointed to the lack of reliable databases of product properties that correspond to local conditions. Hoxha, Haugen and Bjorberg (2017), to propose a list of "green" criteria of material selection to appeal to the wider public, decided to investigate into the understanding of sustainability in Kosovo by means of a survey among nonprofessionals. Rashdan and Ashour (2018) reviewed the literature to define a list of aspects worth consideration in sustainability assessment of interior design products.…”
Section: Type and Number Of Environmental Criteriamentioning
confidence: 99%